Assessment in practice explorations in identity, culture, policy and inclusion - Curtin, Alicia; Cahill, Kevin 1975-; Hall, Kathy 1952-; O'Sullivan, Dan (Current debates in educational psychology, 2020)
"Assessment in Practice explores timely and important questions in relation to assessment. By examining the relationship between identity, culture, policy and inclusion, the book investigates the conflicted and fractured battleground of assessment, and challenges current and practiced understandings of assessment practice. The authors encourage the reader to reconceptualise assessment as a sociocultural practice. Each chapter of the book studies a key theme in the understanding of assessment policy and practice from a sociocultural perspective and provides questions to prompt reflection on the key assessment concepts outlined in the book. Using culture as both a lens and analytic tool, the chapters examine topics such as - The social order of assessment, how assessment works in the world and how learning could be assessed - Perspectives on social justice and assessment, with a particular focus on social class and other potential inequalities on the experiences of assessment for young people - Discussions of ability and the assessment of students with special education needs as well as the role of inclusivity in assessment practice Written by leading academics from University College Cork, the third volume in the successful Routledge Current Debates in Educational Psychology series is an essential read for researchers and postgraduate students in educational research and education psychology"--